Computerization of the Patient History -Patient Answers Compared with Medical Records - Quaak, M. J.; Westerman, R. F.; Schouten, J. A.; Hasman, A.; Bemmel, J. H. van (Methods of Information in Medicine, 1986)
Computerized medical history taking, in which patients answer questions by using a terminal, is compared with the written medical record for a group of 99 patients in internal medicine. Patient complaints were analysed with respect to their frequency of occurrence for all important tracts, such as the respiratory, the gastro-intestinal and the uro-genital tracts. About 36% of over 3,200 patient answers were identical in the patient record and the written record, but a considerable percentage of complaints (56%), that were present in the patient record, were missing in the written record; the reverse was true for 4.5%. A computerized patient record appears to contain more extensive information about patient complaints, still to be interpreted by the experienced physician.
Keywords: Medical Record; Automated Patient History; Problem-oriented Record; Internal Medicine